Western blot using Trypanosoma cruzi chimeric recombinant proteins for the serodiagnosis of chronic Chagas disease: A proof-of-concept study. - Ramona Tavares Daltro; Emily Ferreira Santos; Ângelo Antônio Oliveira Silva; Natália Erdens Maron Freitas; Leonardo Maia Leony; Larissa Carvalho Medrado Vasconcelos; Alejandro Ostermayer Luquetti; Paola Alejandra Fiorani Celedon; Nilson Ivo Tonin Zanchin; Carlos Gustavo Regis-Silva; Fred Luciano Neves Santos (PLoS Neglected Tropical Diseases, 2022)
Background Chagas disease (CD) is caused by Trypanosoma cruzi. The chronic phase of CD is characterized by the presence of IgG anti-T. cruzi antibodies; and diagnosis is performed by serological methods. Because there is no reliable test that can be used as a reference test, WHO recommends the parallel use of two different tests for CD serodiagnosis. If results are inconclusive, samples should be subjected to a confirmatory test, e.g., Western blot (WB) or PCR. PCR offers low sensitivity in the chronic phase, whereas few confirmatory tests based on the WB method are commercially available worldwide. Therefore, new diagnostic tools should be evaluated to fill the gap in CD confirmatory tests. In recent years, four chimeric recombinant antigens (IBMP-8.1, IBMP-8.2, IBMP-8.3 and IBMP-8.4) have been evaluated in phase I, II and III studies using ELISA, liquid microarray and immunochromatography with 95-100% accuracy. Given the high diagnostic performance of these antigens, the present study investigated the ability of these molecules to diagnose chronic CD using a WB testing platform. Methodology/principal findings In this study, we analyzed the diagnostic potential of four chimeric antigens using 40 T. cruzi-positive, 24-negative, and three additional positive samples for visceral leishmaniasis (i.e., potentially cross-reactive) using WB as the diagnostic platform. Checkerboard titration with different dilutions of antigens, conjugated antigens, and serum samples was performed to standardize all assays. All IBMP antigens achieved 100% sensitivity, specificity, and accuracy, with the exception of IBMP-8.3, which had 100% specificity despite lack of significance, but lower sensitivity (95%) and accuracy (96.9%). No cross-reactivity was observed in samples positive for leishmaniasis. Conclusions/significance The present phase I (proof-of-concept) study demonstrated the high diagnostic potential of these four IBMP antigens to discriminate between T. cruzi-positive and -negative samples, making them candidates for phase II and confirmatory testing with WB.